Developing Ni single-atom sites in carbon nitride for efficient photocatalytic H₂O₂ production - Zhang, Xu (2024)
Photocatalytic two-electron oxygen reduction to produce high-value hydrogen peroxide (H2O2) is gaining popularity as a promising avenue of research. However, structural evolution mechanisms of catalytically active sites in the entire photosynthetic H2O2 system remains unclear and seriously hinders the development of highly-active and stable H2O2 photocatalysts. Herein, we report a high-loading Ni single-atom photocatalyst for efficient H2O2 synthesis in pure water, achieving an apparent quantum yield of 10.9% at 420 nm and a solar-to-chemical conversion efficiency of 0.82%. Importantly, using in situ synchrotron X-ray absorption spectroscopy and Raman spectroscopy we directly observe that initial Ni-N3 sites dynamically transform into high-valent O1-Ni-N2 sites after O2 adsorption and further evolve to form a key *OOH intermediate before finally forming HOO-Ni-N2. Theoretical calculations and experiments further reveal that the evolution of the active sites structure reduces the formation energy barrier of *OOH and suppresses the O=O bond dissociation, leading to improved H2O2 production activity and selectivity.